Mineral supplementation of Nelore steers grazing guineagrass pasture - Sousa, J. C. de; Gomes, R. F. C.; Rezende, A. M.; Rosa, I. V.; Cardoso, E. G.; Gomes, A.; Costa, F. P.; Oliveira, A. R. de; Neto, L. Coelho; Curvo, J. B. E. (Pesquisa Agropecuaria Brasileira, 2014)
A study to verify the possible mineral deficiencies in Nelore steers grazing a pasture of guineagrass (Panicum maximum Jacq.) was conducted in the southeastern part of the state of Mato Grosso do Sul, Brazil. The study lasted for 336 days and used 200 steers in the following treatments: A) NaC1 + P + microelements; B) Commercial mixture; C) NaCI + P; and D) NaCl. Many animals in treatment C and D began to loose weight within a few months after initiation of study. Due either to death or poor body conditions, 9 animals from treatment C, and 24 from treatment D were eliminated from the study. The animals in treatments A and B were healthy and thus none was removed. The average weight gain per animal was 143.8 kg for treatment A, 129.9kg for B, 67.7kg for C and 39.8 for treatment D. Biopsy of rib-bone and liver showed that animals from treatments C and D were deficient in P and Zn. The pasture was deficient or borderline in P, Zn, Cu and Co. Soil was poor in, Ca, P, Mg, Zn, Cu and Co. Soil, pasture and animal tissues were all deficient in P and Zn. Economic analysis under risk conditions pointed the superiority of treatment A.